Dari Candaan ke Krisis: Atribusi Tanggung Jawab Publik terhadap Pernyataan Pejabat Negara dalam Pandemi COVID-19 - Rifky Rachmawati Putri; ⁠Rizky Wika Shintya Devi; Ridwan Razib; Sudarto Sudarto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This study examines public attribution of responsibility toward a government official’s humorous statement claiming that “nasi kucing” (a small rice dish) could prevent COVID-19 infection. The incident, which circulated widely through online news portals, sparked public criticism and raised questions about the ethics of crisis communication by state officials. Using a descriptive qualitative approach, this research analyzes news content from several national online media outlets to identify how the public and the media construct responsibility, credibility, and trust. The findings show that the official’s statement was perceived as insensitive and contributed to a communication crisis characterized by irony, satire, and moral outrage. The media framing amplified public attribution of blame, linking the statement to a broader decline in confidence toward governmental communication during the pandemic. This study implies that public officials should employ responsible, empathetic, and evidence-based communication, especially during health crises, to maintain trust and institutional legitimacy. Furthermore, clarity and careful choice of language are key to maintaining public trust and the legitimacy of government institutions during challenging times such as the COVID-19 pandemic.